2011
DOI: 10.1177/0333102410391487
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the calcitonin gene–related peptide gene in trigeminal glia

Abstract: Background The neuropeptide calcitonin gene–related peptide (CGRP) plays a key role in migraine. CGRP gene expression involves an enhancer that is active in neurons, yet inactive in glia. In this report, we analyze epigenetic modifications that allow enhancer activation in glia. Methods DNA methylation and histone acetylation states were measured in rat and human-model cell lines and primary cultures of rat trigeminal ganglia glia. The functional consequence of altering the chromatin state was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 54 publications
0
47
1
Order By: Relevance
“…Examples of epigenetic genes that may regulate CGRP would be genes encoding transcription factors that bind the CGRP gene enhancer or enzymes that modify chromatin structure. The ability of epigenetic reprogramming to activate the CGRP gene in trigeminal glia is supported by cell and organ culture studies (140, 141). In this regard, it may be relevant that valproate, an approved prophylactic drug for migraine (149), can modulate chromatin structure (150).…”
Section: Future Directions: Epistatic Partners and Epigenetic Regulatmentioning
confidence: 96%
See 1 more Smart Citation
“…Examples of epigenetic genes that may regulate CGRP would be genes encoding transcription factors that bind the CGRP gene enhancer or enzymes that modify chromatin structure. The ability of epigenetic reprogramming to activate the CGRP gene in trigeminal glia is supported by cell and organ culture studies (140, 141). In this regard, it may be relevant that valproate, an approved prophylactic drug for migraine (149), can modulate chromatin structure (150).…”
Section: Future Directions: Epistatic Partners and Epigenetic Regulatmentioning
confidence: 96%
“…ROS production following CSD could potentially be involved in epigenetic activation of the CGRP gene, as ROS can activate the gene in cultured trigeminal ganglia (140). Interestingly, the primary product of the CGRP gene in glia is procalcitonin, a CGRP-related peptide that has been reported to be elevated in migraine (141). Researchers are studying whether CSD can activate glial CGRP gene expression.…”
Section: How Does Cgrp Contribute To Migraine?mentioning
confidence: 99%
“…The CGRP antibody (C8198, Sigma) has been previously validated using CGRP knockout mice 30 and by peptide competition with synthetic CGRP prior to IHC 31 . Specificity of proCT antibody (ab53897, Abcam) for proCT compared to calcitonin has been previously reported 24 . Specificity of NeuN mAb A60 antibody (MAB377, Millipore) has been reported 32 .…”
Section: Methodsmentioning
confidence: 93%
“…Transcription factors USF1 and USF2 are activators of the gene 23 , but their ubiquitous expression pattern led to questions about how tissue specificity is maintained. We previously reported that the gene was kept silent in glia through an epigenetic mechanism 24 . Chemical removal of repressive promoter methylation and prevention of histone deacetylation resulted in increased expression from the Calca locus.…”
Section: Introductionmentioning
confidence: 99%
“…For this scenario, we reasoned that the elevated synthesis, if it occurred, would likely be maintained for a relatively long time (24 hours). Similar prolonged times were also required for activation of CGRP gene expression in trigeminal ganglia organ cultures (26), and by epigenetic reprogramming of glial cells (27). We therefore proposed that CSD might be a mechanism by which cortical levels of CGRP become elevated for a prolonged period in migraine and TBI patients.…”
Section: Introductionmentioning
confidence: 86%